THE INFLUENCE OF WORK ENVIRONMENT AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT BANK BJB, DAAN MOGOT BRANCH, WEST JAKARTA - Kalumidya Erponis, Nuru; Hardiantini, Ela; Septiani, Yeni (International Journal of Multidisciplinary Research and Literature, 2025)
The purpose of this study is to determine the influence of the work environment and work discipline on employee performance at Bank BJB's Daan Mogot branch in West Jakarta. The research approach used in this study is quantitative. The sampling technique used in this study was saturated sampling with a sample size of 83 employees. Data collection techniques used were questionnaires distributed to employees at Bank BJB's Daan Mogot branch in West Jakarta. Data analysis techniques used descriptive analysis, validity testing, reliability testing, multiple regression analysis, classical assumption testing, partial t-test, simultaneous F-test, and coefficient of determination (R2). Data processing in this study used SPSS version 26 for Windows. This study found a positive and significant effect of Variable X1 (Work Environment) on Variable Y (Employee Performance), meaning that if the Work Environment at Bank BJB Daan Mogot Branch in West Jakarta is improved, Employee Performance will increase. There is a positive and significant effect of Variable X2 (Work Discipline) on Variable Y (Employee Performance), meaning that if Work Discipline at Bank BJB Daan Mogot Branch in West Jakarta is improved, Employee Performance will increase and improve. There is a positive and significant effect of the Work Environment (X1) and Work Discipline (X2) on Employee Performance (Y) at the α level of 0.05, meaning that if the Work Environment and Work Discipline at Bank BJB Daan Mogot Branch in West Jakarta are improved, Employee Performance will be maximized.